1966
DOI: 10.21236/ad0629955
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transfer and First-Order Boundary -Layer Effects on Sharp Cone Drag

Abstract: A theoretical model is developed based on an iterated perfect gas inviscid-viscous flow field which includes first-order displacement {viscous interaction), transverse curvature, wall slip, and temperature jump in addition to mass transfer effects. The effects of inviscid (tangent cone) and viscous (nonsimilar laminar boundary layer) flow field matching conditions are also considered. Numerical results are compared with experimental and analytical results of King and Talbot (AI A A J., 1964) for a 5-deg half-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1966
1966
1970
1970

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…21 and from comparing numerical and experimental results that the conical shock expansion method was superior to the tangent cone method for calculating the inviscid edge conditions for the boundary-layer solution. The experimentally measured 6 and numerically calculated effects of nitrogen injection on the total drag of a 9° half-angle cone at the three Mach number-Reynolds number conditions used at the AEDC-VKF are shown in Fig. 8.…”
Section: Aedc-vkf Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 and from comparing numerical and experimental results that the conical shock expansion method was superior to the tangent cone method for calculating the inviscid edge conditions for the boundary-layer solution. The experimentally measured 6 and numerically calculated effects of nitrogen injection on the total drag of a 9° half-angle cone at the three Mach number-Reynolds number conditions used at the AEDC-VKF are shown in Fig. 8.…”
Section: Aedc-vkf Conditionsmentioning
confidence: 99%
“…Their data also showed significant drag reductions caused by gas injection, and, furthermore, they showed that for a given mass injection rate air was more effective than helium in reducing the drag on the cone. Investigations 6 have been made at the Arnold Engineering Development Center's von Karman Gas Dynamics Facility (AEDC-VKF) of the effects of normal injection of nitrogen through a porous wall into the boundary layer on a sharp 9°h alf-angle cone at Mach ~ 10 and freestream Reynolds numbers of approximately 400, 1750, and 2750/in. Again, appreciable drag reduction was shown with gas injection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure has the drawback that the solution is needed for y < A* to continue with the second order boundary-layer term, as evidenced by (5) . If only the second order outer solution is needed, this approach may be advantageous.…”
mentioning
confidence: 99%
“…, All terms involving the arbitrary quantity d then cancel, and (v e /u e ) can be evaluated easily. In a recent paper Lewis et al 5 have considered a numerical example for which all the terms in the Li and Gross transverse-curvature formula are examined. The authors make the following statement, "We note that the effect of the terms neglected by Li and Gross under the hypersonic approximation caused a 40% and 50% change in isaa.~1(dd*/dx) at Moo = 5.64 and 10, respectively."…”
mentioning
confidence: 99%